PERAN PENDIDIK DALAM MEMBANGKITKAN KETERTARIKAN MEMBACA DI KALANGAN SISWA SEBAGAI PENCIPTA LINGKUNGAN BELAJAR YANG KONDUSIF - Agus Salim (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2022)
This research explores the crucial role of educators in shaping students' interest in reading with a focus on creating a conducive learning environment. A conducive learning environment is a key factor in stimulating students' reading interest and assisting them in developing sustainable reading habits. In this context, the role of teachers as primary facilitators in creating a stimulating and supportive learning environment for reading interest becomes highly significant. This study outlines strategies and practices that educators can employ to create a conducive learning environment for the development of students' reading interest. Through this approach, a significant increase in students' participation in reading activities and improvement in their overall literacy is expected